Soft tissue tenodesis of the long head of the biceps tendon associated to the Roman Bridge repair - Maffulli Nicola (BMC Musculoskeletal Disorders, 2008)
Abstract Background Rotator cuff tears are frequently associated with pathologies of the long head of the biceps tendon (LHBT). Tenotomy and tenodesis of the LHBT are commonly used to manage disorders of the LHBT. Methods We present an arthroscopic soft tissue LHBT tenodesis associated with a Roman Bridge (double pulley – suture bridges) repair Results Two medial row 5.5-mm Bio-Corkscrew suture anchors (Arthrex, Naples, FL), double-loaded with No. 2 FiberWire sutures (Arthrex, Naples, FL), are placed in the medial aspect of the footprint. A shuttle is passed through an anterior point of the rotator cuff and through the LHBT by means of a Penetrator or a BirdBeak suture passer (Arthrex, Naples, FL). A tenotomy of the LHBT is performed. All the sutures from the anteromedial anchor are passed through a single anterior point in the rotator cuff using a shuttle technique. All the sutures from the posteromedial anchor are passed through a single posterior point in the rotator cuff. The sutures in the medial row are tied using the double pulley technique. A suture limb is retrieved from each of the medial anchors and manually tied as a six-throw surgeon's knot over a metal rod. The two free suture limbs are pulled to transport the knot over the top of the tendon bridge. The two free suture limbs are then used to produce suture bridges over the tendon, using a Pushlock (Arthrex, Naples, FL), placed 1 cm distal to the lateral edge of the footprint. The same double pulley – suture bridges technique is repeated for the other two suture limbs from the two medial anchors. Conclusion This technique allows to perform a double pulley – suture bridges repair for a rotator cuff tear, associated with a soft tissue tenodesis for the management of LHBT pathology. The tenodesis of the LHBT is performed just with the passage of a shuttle inside the LHBT, after passing it through the anterior portion of the rotator cuff, with successive detachment of the LHBT from the glenoid. It is a technically easy procedure which can be performed relatively quickly, and does not require additional fixation.